Protection, concentration, and the direction of foreign investments - De Dios, Emmanuel S. (1986)
This paper attempts mainly to substantiate the hypothesis that the pattern of tariff protection in the past contributed to the oligopolistic structure of Philippine manufacturing, and that such concentration included a distinct foreign element. Firstly, the paper presents a theory to illustrate the effects of foreign capital inflows on the country's resource allocation assuming their tendency to be monopolistic. It then tested the following relationships: 1) between value added concentration ratios and effective rate of protection as well as other standard variables explaining industrial concentration, 2) between levels of concentration and levels of industrial or firm profitability, and 3) between foreign capital and seller concentration. The findings imply that, for the periods covered, effective tariff protection did exert an influence in promoting seller concentration. Results also suggested that it influenced the degree of international investments as well; as significant degree of association emerged between those sectors which were characterized by heavy seller concentration, and those in which foreign capital found a hospitable niche. The study interprets these findings for their significance to policy making and development theory.
Keywords: Tariff -- Law and legislation; Foreign investments; Dealers (Retail trade)